Effect of elevated CO2 and elevated temperature on growth and biomass accumulation in Valeriana jatamansi Jones. under different nutrient status in the western Himalaya - MUNISH KAUNDAL; RAKESH KUMAR (Journal of Agrometeorology, 2020)
Valeriana jatamansi is an important medicinal and aromatic plant used as sedative in modern  and traditional medicines butthere is dearth of literature regarding how elevated CO2 and temperature affect on this plant. Therefore,an experiment was conducted to study the effect of elevated CO2 (550±50 µmol mol-1) and elevated temperature (2.5±0.5°C above ambient) and vermicompost on growth, phenology and biomass accumulation in V. jatamansi under Free Air CO2 Enrichment (FACE) and Free Air Temperature Increment (FATI) facilities at Palampur, India, during 2013-2015. Growth parameters and biomass accumulation into different parts were observed at 4, 12 and 16 months after exposure (MAE). Plant height, total dry biomass and leaf area plant -1 increased in elevated CO2 treatment applied with vermicompost as compared to the other treatments. Elevated CO2 significantly enhanced leaf area (3.5- 23.5%), leaf biomass (12.7-33.2%), stem (15.3-15.6%), root (3.2-72.5%), rhizome (2.1-42.2%) and total biomass (7.7-52.7%), whereas elevated temperature increased aboveground biomass (15.0-45.3%), belowground biomass (11.6-55.5%) and total biomass (12.4-7.9%), respectively, as compared to ambient. Phenological stages were advanced by 1.2-3.9 days under FACE and FATI as compared to ambient. The results indicate that aboveground, belowground and total biomass increased under elevated CO2 and elevated temperature as compared to ambient.